2008
DOI: 10.1128/jvi.01329-08
|View full text |Cite
|
Sign up to set email alerts
|

Biogenesis of Cytoplasmic Membranous Vesicles for Plant Potyvirus Replication Occurs at Endoplasmic Reticulum Exit Sites in a COPI- and COPII-Dependent Manner

Abstract: Single-stranded positive-sense RNA viruses induce the biogenesis of cytoplasmic membranous vesicles, where viral replication takes place. However, the mechanism underlying this characteristic vesicular proliferation remains poorly understood. Previously, a 6-kDa potyvirus membrane protein (6K) was shown to interact with the endoplasmic reticulum (ER) and to induce the formation of the membranous vesicles. In this study, the involvement of the early secretory pathway in the formation of the 6K-induced vesicles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
154
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(168 citation statements)
references
References 83 publications
(144 reference statements)
7
154
0
2
Order By: Relevance
“…By contrast, the viral protein 6 kDa protein 2 (6K 2 ) of tobacco etch virus (TEV) and turnip mosaic virus (TuMV) is responsible for initiating the assembly of 6K 2 -induced vesicles (6K 2 -vesicles). These vesicles serve as VRCs, exit ER membranes and eventually assemble into large granule structures at chloroplasts in addition to playing a possible role in cell-to-cell movement (Cheng et al, 2015;Cotton et al, 2009;Jiang et al, 2015;Wei and Wang, 2008;Wei et al, 2010). Out of the three Arabidopsis Sec24 isoforms (Sec24a, Sec24b and Sec24c) (Marti et al, 2010), 6K 2 interacts with Sec24a to assemble 6K 2 -vesicles at ER exit sites (ERES).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the viral protein 6 kDa protein 2 (6K 2 ) of tobacco etch virus (TEV) and turnip mosaic virus (TuMV) is responsible for initiating the assembly of 6K 2 -induced vesicles (6K 2 -vesicles). These vesicles serve as VRCs, exit ER membranes and eventually assemble into large granule structures at chloroplasts in addition to playing a possible role in cell-to-cell movement (Cheng et al, 2015;Cotton et al, 2009;Jiang et al, 2015;Wei and Wang, 2008;Wei et al, 2010). Out of the three Arabidopsis Sec24 isoforms (Sec24a, Sec24b and Sec24c) (Marti et al, 2010), 6K 2 interacts with Sec24a to assemble 6K 2 -vesicles at ER exit sites (ERES).…”
Section: Discussionmentioning
confidence: 99%
“…This can be through: (i) a viral protein possessing a transmembrane domain, as in the case of the 6 kDa protein of potyviruses (Schaad et al, 1997;Wei & Wang, 2008;Wei et al, 2010); (ii) interaction with an integral membrane protein from the host, as in the case of TMV, which requires the transmembrane proteins TOM1 and TOM3 (Yamanaka et al, 2000(Yamanaka et al, , 2002; and (iii) monotopic membrane association by a virus-encoded protein containing an IPM anchor (an amphipathic a-helix), as in the case of SFV (Salonen et al, 2005;Spuul et al, 2007) and BMV (Liu et al, 2009). An amphipathic a-helix contains a hydrophobic face that inserts into one leaflet of the lipid bilayer, thus achieving integral membrane association (Sapay et al, 2006;Spuul et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, uncoating of the viral RNAs in the cytoplasm, translation of the polyprotein and replication of the viral genome occur. Accumulated evidence suggests the replication of eukaryotic positive-strand RNA viruses including plant potyviruses is associated with intracellular membranous structures (Wei and Wang, 2008). These membranous vesicles have been proposed to provide a scaffold for anchoring the virus replication complex (VRC), confine the process of RNA replication to a specific safeguarded cytoplasmic location to prevent the activation of host defense responses, and to recruit the components required for replication and maintain the proper concentrations of these components (Wileman, 2006).…”
Section: Smv Replicationmentioning
confidence: 99%
“…It has been shown that in potyvirus-infected plant cells, these vesicular compartments contain a number of host proteins, i.e., heat shock cognate 70-3 (Hsc70-3), poly(A)-binding protein (PABP), eEF1A and eIF(iso)4E, and several non-structural viral proteins, such as the 6K2, NIb (the viral RNA dependent RNA polymerase, RdRp), NIa (including NIa-VPg or NIa-Pro or as a precursor protein) and CI Thivierge et al, 2008;Cotton et al, 2009;Wei et al, 2010a). The 6K2 (also called 6K) protein is an integral membrane protein that induces the formation of 6K-containing membranous vesicles at ERES (Wei and Wang, 2008). These ER-derived vesicles further target chloroplasts where they amalgamate and induce chloroplast membrane invaginations (Wei and Wang, 2008;Wei et al, 2010a).…”
Section: Smv Replicationmentioning
confidence: 99%
See 1 more Smart Citation